Islamic Finance and Digital Currencies: An Overview The development of Blockchain adoption in Iraq and Arab countries - Alhchaimi, Mawj Abbas Jasim; Hashim, Hasan Talib (University of Thi-Qar Journal, 2025)
This review paper provides a comprehensive examination of blockchain technology in Arab countries. This article examines the prospective uses of blockchain technology across several domains, including banking and public service delivery. The document delineates the limitations and opportunities associated with the use of blockchain technology in Arab nations, emphasizing the prospective advantages of this technology for the area, including improved communication, safety, and efficiency. The paper concludes with an examination of the future potential of blockchain technology in Arab nations, alongside the need for continuous research and development in this domain. This report enhances comprehension of blockchain technology's significance in Arab nations and provides insights to aid policymakers and business leaders in optimising its maximum potential